Use of portable single‐lead electrocardiogram device as an alternative for QTc monitoring in critically ill patients - Martin Rebolledo‐Del Toro; Ana Beatriz Carvajalino‐Galeano; Clarena Pinto‐Brito MD; Oscar Mauricio Muñoz‐Velandia; Ángel Alberto García‐Peña (Annals of Noninvasive Electrocardiology, 2024)
Abstract Purpose Acquired QT prolongation is frequent and leads to a higher mortality rate in critically ill patients. KardiaMobile 1L® (KM1L) is a portable, user‐friendly single lead, mobile alternative to conventional 12‐lead electrocardiogram (12‐L ECG) that could be more readily available, potentially facilitating more frequent QTc assessments in intensive care units (ICU); however, there is currently no evidence to validate this potential use. Methods We conducted a prospective diagnostic test study comparing QT interval measurement using KM1L with conventional 12‐L ECG ordered for any reason in patients admitted to an ICU. We compared the mean difference using a paired t‐test, agreement using Bland–Altman analysis, and Lin's concordance coefficient, numerical precision (proportion of QT measurements with <10 ms difference between KM1L and conventional 12‐L ECG), and clinical precision (concordance for adequate discrimination of prolonged QTc). Results We included 114 patients (61.4% men, 60% cardiovascular etiology of hospitalization) with 131 12‐L ECG traces. We found no statistical difference between corrected QT measurements (427 ms vs. 428 ms, p = .308). Lin's concordance coefficient was 0.848 (95% CI 0.801–0.894, p = .001). Clinical precision was excellent in males and substantial in females (Kappa 0.837 and 0.781, respectively). Numerical precision was lower in patients with vasoactive drugs (−13.99 ms), QT‐prolonging drugs (13.84 ms), antiarrhythmic drugs (−12.87 ms), and a heart rate (HR) difference of ≥5 beats per minute (bpm) between devices (−11.26 ms). Conclusion Our study validates the clinical viability of KM1L, a single‐lead mobile ECG device, for identifying prolonged QT intervals in ICU patients. Caution is warranted in patients with certain medical conditions that may affect numerical precision.